Parametric rationing with uncertain needs - LONG, Yan (Institutional Knowledge at Singapore Management University, 2019)
We study resource allocation in the face of uncertain needs. We extend Young (1987)’s parametric rules to the uncertain context. We re-establish the axiomatic char-acterization of parametric rules and show the optimality of the rules.